Pengaruh Desentralisasi dan Karakteristik Informasi Sistem Akuntansi Manajemen terhadap Kinerja Manajerial - Ietje Ietje Nazaruddin (The Indonesian Journal of Accounting Research, 2013)
This study examines the interactive effect of management accounting systems design and decentralization on managerial performance. Management accounting systems design was defined in term of perceived availability of characteristics of information, namely, broad scope, timeliness, aggregation and level of integration. Decentralization refers to the level autonomy delegated to the managers.Responses of 66 managers (production and marketing) were analyzed by using the regression models with two-way interaction. In addition, an analytical method of utilizing partial derivative to test the contingency relationship as advocated by Schoonhoven (1981) and Govindarajan (1986) was also used.The results provide support for the hypothesis that decentralization and information characteristics of management accounting systems have an interactive effect on managerial performance. More specifically, the results showed that decentralization significantly moderates the relationship between information characteristic management accounting systems and managerial performance. The greater the degree of decentralization, the stronger the effect of high degrees of sophisticated information characteristics on managerial performance. Keywords :     decentralization, management accounting systems, broad scope, timeliness, aggregation, integration and performance